Measurement of holistic well-being among Japanese retirees in Malaysia: a framework - Alby, Jeffrey Lawrence D'Silva; Abu Samah, Asnarulkhadi (International Society for Development and Sustainability, 2017)
In this era of globalization and borderless world, the well-being of the community is given much prominence as a weapon in ensuring sustainable community development and a better livelihood for mankind. The focus of this paper is to identify the possible factors that could be used to evaluate on the well-being among Japanese retirees residing in Malaysia. A thorough search of the existing literature was used to collect data. The results showed that well-being is better measured if we could combine both the objective and subjective dimensions and the dimensions could vary based on the concerned community. Various factors were recognized to measure the holistic well-being among Japanese retirees in Malaysia and this could be a yardstick for future researchers that are embarking studies on retirees living away from the homeland.